Public Vs. Private Health Care Services Demand in Italy - Daniele Fabbri; Chiara Monfardini (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2002)
In this paper we use data coming from the new Italian Survey on Health Ageing and Wealth (SHAW) to analyse physician services utilization in Italy explicitly acknowledging the existence of two different classes of providers: public and private. We consider visits by a specialist physician as the measure of individual services utilization. In particular we assess the relative importance of variables like income, education, private insurance and supply characteristics as determinants of the utilization of such services, while controlling for individual health and need. We do that by estimating some alternative count data regression models of which we discuss the relative advantages and disadvantages and the entailed different interpretation of the results.
Keywords: 330